Two complete finitary sequent calculi for reflexive common knowledge - Girčys, Aurimas Paulius; Pliuškevičius, Regimantas (Lietuvos matematikos rinkinys, 2013)
This paper discusses the use of complete sequent calculi for reflexive common knowledge logic. Description of language and complete infinitary calculus for RCL is presented. Then finitary calculi RCLI and RCLL are introduced and completeness of finitary calculi RCLI and RCLL is proven.